Endogenous Endophthalmitis Caused by Prototheca Microalga in Birman Cat, Spain - Laura Jimenez-Ramos; Ana Ripolles-Garcia; Gianvito Lanave; Francesco Pellegrini; Miriam Caro-Suarez; Almudena Latre-Moreno; Marta Ferruz-Fernandez; Maria Luisa Palmero-Colado; Vanessa Carballes-Perez; Antonio Melendez-Lazo; Carolina Naranjo; Fernando Laguna; et al. (Emerging Infectious Diseases)
We identified Prototheca spp. microalga in ocular samples of a cat in Spain with nontreatable endogenous endophthalmitis. Within 2 years, the eye lesions progressively worsened and neurologic signs appeared, suggesting systemic spread of the infection. On multitarget sequence analysis, the feline pathogen could not be assigned to any known Prototheca species.